Gold Nanoparticle-Based Therapy for Muscle Inflammation and Oxidative Stress - Pinho RA; Haupenthal DP; Fauser PE; Thirupathi A; Silveira PCL (Dove Medical Press, 2022)
Ricardo A Pinho,1,2 Daniela PS Haupenthal,3 Paulo Emílio Fauser,3 Anand Thirupathi,2 Paulo CL Silveira3 1Laboratory of Exercise Biochemistry in Health, Graduate Program in Health Sciences, School of Life Sciences and Medicine, Pontifícia Universidade Católica Do Paraná, Curitiba, Paraná, Brazil; 2Faculty of Sports Science, Ningbo University, Ningbo, People's Republic of China; 3Laboratory of Experimental Pathophysiology, Graduate Program in Health Sciences, Universidade Do Extremo Sul Catarinense, Criciúma, Santa Catarina, BrazilCorrespondence: Ricardo A Pinho, Laboratory of Exercise Biochemistry in Health, Graduate Program in Health Sciences, School of Life Sciences and Medicine, Pontifícia Universidade Católica do Paraná, Imaculada Conceição Street, 1155, Prado Velho, Curitiba, Paraná, Zip Code 80215-901, Brazil, Email rapinho12@gmail.comAbstract: Proinflammatory cytokines and reactive oxygen species are released after muscle damage, and although they are necessary for the muscle regeneration process, an excess of these substances leads to the destruction of biomolecules and impairment of the repair system. Several drugs have emerged in recent years to control the muscle inflammatory response, and studies have shown that gold nanoparticles (AuNPs) have anti-inflammatory and antioxidant properties. This review reveals the effects of AuNPs on the inflammatory and redox mechanisms of muscles. We assessed the results of several studies published in different journals over the last 20 years, with a focus on the effects of AuNPs on possible aspects of muscle regeneration or recovery, namely, inflammatory processes and redox system mechanisms. A systematic database search was conducted using PubMed, Medline, Bireme, Web of Science, and Google Scholar to identify peer-reviewed studies from the 2000s. Combinations of keywords related to muscle damage, regeneration or repair, AuNPs, oxidative stress, and antioxidants were used in the search. This review did not address other variables, such as specific diseases or other biological effects; however, these variables should be considered for a complete understanding of the effects of AuNPs on skeletal muscles.Keywords: gold nanoparticles, redox homeostasis, antioxidant, muscle regeneration, inflammation, nanomaterials, oxidative stress